Genotoxicity evaluation of alpha-linolenic acid-diacylglycerol oil. (2016) - Honda, Hiroshi; Fujita, Yurika; Hayashi, Aya; Ikeda, Naohiro; Ito, Yuichi; Morita, Osamu
Highlights: We evaluated the genotoxicity of ALA-DAG oil using standard tests. Bacterial reverse mutation and in vitro / in vivo micronucleus tests were conducted. No genotoxicity was observed under the testing conditions. Abstract: The alpha-linolenic acid (ALA)-diacylglycerol (DAG) oil is an edible oil enriched with DAG (>80%) and ALA (>50%). Although DAG oil, which mainly consists of oleic and linoleic acids has no genotoxic concerns, the fatty acid composition could affect the chemical property of DAG. Therefore, the purpose of this study was to evaluate the genotoxicity of ALA-DAG oil using standard genotoxicity tests in accordance with the OECD guidelines. ALA-DAG oil showed negative results in the bacterial reverse mutation test (Ames test) and in vitro micronucleus test in cultured Chinese hamster lung cells with and without metabolic activation, and in the in vivo bone marrow micronucleus test in mice. Our results did not show any genotoxicity, suggesting that the fatty acid composition had no deleterious effects. We conclude that ALA-DAG oil had no genotoxicity concerns under the testing conditions.